Konsep Ukhuwah Islamiyah Dalam Al-Qur’an Studi Analisis Kompratif Tafsir Ibnu Kasir dan Tafsir Al-Misbah QS. Al-Hujurat Ayat 10 - As’ari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The establishment of ukhuwah is not only a normative text but must be applied in life, seeing the fact now that Muslims are stagnant due to the fading sense of brotherhood, it arises because of the frequent differences among Muslims that trigger divisions, the Qur'an has underlined that difference is the law that applies in this life, In addition to the difference is a divine will also for the sake of survival , at the same time in order to achieve the goal of life of beings on the stage of the earth. To establish ukhuwah Islamiah needed is not just an explanation of aspects of equality in religious views or just tolerance concerning differences of views. More important, however, are the joint measures implemented by different leaders and muballighs in their view. While Ukhuwah according to Ibn Kathir is a brotherly relationship established on the basis of religion. While according to M. Quraish Shihab Ukhuwah Islamiah is an Islamic brotherhood or brotherhood taught by Islam